DINAMIKA KELOMPOK PADA USAHA IKAN LELE SANGKURIANG (Clarias Gariepinus) KELOMPOK BUDIDAYA IKAN ‘’KARYA SEJATI’’ DI KELURAHAN SAMBUTAN KOTA SAMARINDA - Rismayani; Eko Sugiharto; Gusti Haqiqiansyah (Jurnal Pembangunan Perikanan dan Agribisnis, 2022)
purpose of this study was to determine the characteristics and level of group dynamics among members of the Karya Sejati group. The research was conducted in Sambutan Village, Samarinda City. The sample method used is a purposive sampling method and the data analysis used is descriptive qualitative analysis and Likert scale. The results of the analysis show the characteristics of POKDAKAN Karya Sejati in Sambutan Village including age characteristics from 35-44 years, the highest formal education at the SMA/SMK level, the highest non-formal education at 3-4 times attending meetings, the highest income between Rp. 1,600,000 - Rp. 2.100.000,-, and the duration of joining the group is about 5-6 years, as well as the management and group members are married. The level of group dynamics based on indicators of group goals scores 9, group structure scores 9, task function scores 8.7, group development and coaching scores 7.9, group cohesiveness scores 7.9, group atmosphere scores 8.6, and group pressure scores 9, all of these indicators are in the high category. Based on the indicator of group effectiveness, a score of 6.8 and hidden intent, a score of 5.7, both indicators are in the medium category. And overall the dynamic level of POKDAKAN Karya Sejati cumulatively has a score of 72.6, which is in the high category. Keywords: Group Dynamics, Cultivation Group, Catfish Business.